2005
DOI: 10.1002/macp.200500147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymers to Study the Influence of the Azobenzene Content on the Photo‐Induced Surface Relief Grating Formation

Abstract: Summary: The influence of the azobenzene concentration on the photo‐induced surface relief grating (SRG) formation in polymer films was investigated. Two series of polymers with 4‐alkoxy‐4′‐cyanoazobenzene side groups were synthesized. In series A, the degree of substitution was varied, while in series B, azobenzene and biphenyl groups were introduced in varying composition, but the concentration of non‐reacted HEMA‐groups was kept constant. Photo‐induction of the dichroism and the SRG was studied as function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Similar concentration dependence in the SRG modulation depth as shown in Figure b has been reported also in covalently functionalized azo-polymers by Fukuda et al and Börger et al On the contrary, Andruzzi et al have reported on dramatic suppression of the surface relief in side-chain polymethacrylates at azobenzene concentrations exceeding 75 mol %, probably due to existence of LC phases at high degree of functionalization, and Priimagi et al reported on the linear increase in the surface-modulation depth up to equimolar complexation in amorphous polymer–monoazo complexes . The fact that the concentration dependence of SRG formation differs considerably for different azobenzene-containing materials serves to highlight the complicated nature of this photomechanical effect, which is not comprehensively understood up to date.…”
Section: Resultssupporting
confidence: 82%
“…Similar concentration dependence in the SRG modulation depth as shown in Figure b has been reported also in covalently functionalized azo-polymers by Fukuda et al and Börger et al On the contrary, Andruzzi et al have reported on dramatic suppression of the surface relief in side-chain polymethacrylates at azobenzene concentrations exceeding 75 mol %, probably due to existence of LC phases at high degree of functionalization, and Priimagi et al reported on the linear increase in the surface-modulation depth up to equimolar complexation in amorphous polymer–monoazo complexes . The fact that the concentration dependence of SRG formation differs considerably for different azobenzene-containing materials serves to highlight the complicated nature of this photomechanical effect, which is not comprehensively understood up to date.…”
Section: Resultssupporting
confidence: 82%
“…The driving mechanism depends both on the experimental parameters and the material itself, and a universal theory is still under debate. Furthermore, a thorough understanding on how the polymer structure affects the surface patterning efficiency has not been reached. Known important parameters include molecular weight and the glass transition temperature of the polymer, , as well as the azobenzene content of the material. The effect of chromophore concentration is particularly interesting as it can help to gain fundamental understanding on how much power the azobenzene isomerization reaction can actually translate into large macroscopic movements. The concentration dependence of mass transport efficiency has been studied in many systems with intermediate or high azobenzene concentrations.…”
mentioning
confidence: 99%
“…The concentration dependence of mass transport efficiency has been studied in many systems with intermediate or high azobenzene concentrations. Andruzzi et al and Börger et al reported an optimum degree of functionalization on the order of 75 mol %, above which the efficiency of SRG formation decreases due to intermolecular interactions between adjacent chromophores. Moreover, Fukuda et al reported an exponential increase of the surface modulation depth as a function of dye content up to 50 wt %, after which the depth remained constant.…”
mentioning
confidence: 99%
“…Having highlighted that SRG can come in almost all shapes and sizes, we continue hereafter by making a list of the wide variety of polymeric backbones that have been used over the years to create them. The most used polymers are based on polyacrylates, , especially the commercially available poly­(disperse red 1 methacrylate) (pDR1m) (Figure a). pDR1m has the advantage of bearing a push–pull azobenzene derivative, with absorption spectra partially overlapped for the trans and cis isomers.…”
Section: Motion From Photochromic Molecular Switchesmentioning
confidence: 99%